Technical and Financial Analysis of Squid Fishing - Abdul Hafidz Olii (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2020)
This study aims to determine the technicality of catching and to analyze the finances of the squid fishing effort in Luwoo Village, Posigadan District, Bolaang Mongondow Selatan Regency. The method used in this research is descriptive method. Sampling using survey and interview methods. Primary data obtained through direct observation and conducting interviews with respondents using a questionnaire. Technically, the fishing gear used by fishermen in Luwoo Village still uses relatively traditional technology by relying on knowledge from generation to generation. The use of the squid fishing gear is the result of a modification between the roller, fishing line, light-stick, swivel and squid fishing gear. The totabito or squid fishing line is extended 3-5 meters using a light-stick as an attractor to attract the squid. Financially, the squid fishing business has an average R/C value of 2.2 (> 1), a payback period of 0.8 years and an average net profit of Rp. 11,959,200 per year or about 121.77%. So, from a financial perspective, the squid fishing business in Luwoo Village can be said to be profitable. Keywords: Squid; squid fishing; technical; financial.